Formation of the Dark Matter–Deficient S0 Galaxy NGC 4111 under the Tidal Interactions - Mei Ai; Ming Zhu; Nai-ping Yu; Jin-long Xu; Xiao-lan Liu; Yingjie Jing; Qian Jiao; Yao Liu; Chuan-peng Zhang; Jie Wang; Peng Jiang (The Astrophysical Journal Letters)
We present high-sensitivity and large-scale atomic hydrogen (H i ) observations toward lenticular (S0) galaxy NGC 4111 using the Five-hundred-meter Aperture Spherical Radio Telescope. The column-density map shows that NGC 4111 and seven other different types of galaxies share a huge H i gas complex. The data also suggest that NGC 4111 is interacting with seven galaxies. Moreover, we identified a rotating gas disk associated with NGC 4111 from the H i complex. Still, the H i disk rotation direction has deviated from its stellar disk by about 34 $\mathop{.}\limits^{\unicode{x000b0}}$ 2, indicating that the NGC 4111 galaxy is undergoing a transition from a spiral galaxy to an S0 galaxy by the tidal interactions. The obtained dark matter to stellar mass ratio of NGC 4111 is 3.1 ± 0.7, which is lower than the average value of the local Universe, implying that the interactions may strip its dark matter. Our results suggest that in a galaxy group environment, tidal interactions have a significant effect on galaxy features.